Strategi Belajar Mandiri Orang Dewasa di Era Digital: Analsiis Bibliometrik dan Systematic Literature Review - Alwis Sukmawati; Nurlaela Hamidah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze self-directed learning strategies in adult education in the digital age through a bibliometric analysis and a systematic literature review (SLR). the study is motivated by the development of digital technology. The phenomenon of globalization, as well as the increasing need for lifelong learning among adults. The research methodology floows the PRISMA guideline to identify, screen, evaluate, and synthesize relevant scintific article from 2017-2026. Data collection was conducted using Google Scholar with the assistance of the Publish or Perish application, while bibliometic analysis was performed using VOSviewer sofwere. The results indicate that research on self-directed learning in adult education has shown a significant increase and is closely related to digital learning, lendend learning, learning management systems (LMS), MOOC, digital literacy, and andragogical approaches. Biblimetric visualization indicates that techology-based self-drected learning has become a major topic in recent years. The resulats of the systematic literature review show that self-directed learning strategies have a positive impact on increasing independence, learning motivation, flexibility, problem-solving skills, and lifelong learning among adults. Digital techology also plays a siginificant role in facilitating accese to information and creating more adaptive learning experinces. Furthermore, success in self-directed learning also depends on digital literacy levels, intrinsic motivation, metacognitive skill, and adequate learning environment support. Therefore, is is crucial adult education institution to integrate technology-based learning with andragogical approaches to support efective self-directed learning in the digital age